2024
DOI: 10.1001/jama.2024.0001
|View full text |Cite
|
Sign up to set email alerts
|

Whose Responsibility Is It to Define Exceptions in Abortion Bans?

Carmel Shachar,
Susannah Baruch,
Louise P. King

Abstract: This Viewpoint evaluates Texas’ proposals to define the scope of the life exception for the state’s abortion ban and argues that these approaches do not allow physicians to follow the national standards of care, avoid criminal liability, or have sufficient notice of what the law permits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In discussions of a patient’s candidacy for a health or life exception to the abortion ban, tensions may arise between OB-GYNs and hospital legal counsel due to differences in approaches to risk in obstetrics (in which threats to both the pregnant patient and the fetus occur along a spectrum) and in law (in which decisions about legality are binary) . Tensions may be overcome by explicitly acknowledging what all parties share—namely, frustrations with the vagueness of state laws and the mutual discomfort that comes from making a high-stakes decision without legal precedents.…”
Section: Medicolegal Collaborationmentioning
confidence: 99%
“…In discussions of a patient’s candidacy for a health or life exception to the abortion ban, tensions may arise between OB-GYNs and hospital legal counsel due to differences in approaches to risk in obstetrics (in which threats to both the pregnant patient and the fetus occur along a spectrum) and in law (in which decisions about legality are binary) . Tensions may be overcome by explicitly acknowledging what all parties share—namely, frustrations with the vagueness of state laws and the mutual discomfort that comes from making a high-stakes decision without legal precedents.…”
Section: Medicolegal Collaborationmentioning
confidence: 99%
“…The ability of clinicians to determine the lawfulness of any abortions provided is important for protecting clinicians and patients who use medical necessity exceptions to abortion bans. To date, there has been significant litigation, especially in Texas, around the scope of these exceptions . While the Texas Supreme Court has suggested that the medical profession should determine when an abortion could be provided under this exception, in that same case, the court substituted its own judgment about the danger to the patient for that of the physician .…”
Section: The Importance Of Who Determines Lawful Reproductive Care Se...mentioning
confidence: 99%
“…To date, there has been significant litigation, especially in Texas, around the scope of these exceptions . While the Texas Supreme Court has suggested that the medical profession should determine when an abortion could be provided under this exception, in that same case, the court substituted its own judgment about the danger to the patient for that of the physician . Using the new Reproductive Privacy Rule, clinicians could determine that an abortion was lawfully provided under a medical necessity exception and refuse to disclose records to law enforcement.…”
Section: The Importance Of Who Determines Lawful Reproductive Care Se...mentioning
confidence: 99%